Teams with lower injury rates have greater success in the Currie Cup rugby union competition - Starling, L (South African Journal of Sports Medicine, 2019)
Background: Professional football teams that rank high on the log at the end of the season generally have fewer injuries than teams that rank lower on the log. This highlights the importance of implementing injury prevention measures, not only to protect player welfare and ensure their longevity in the sport, but also to improve the performance of the team. The association between a low incidence of injury and superior performance during a season may be even more relevant in sports with a higher incidence of injury than football, such as rugby union. Discussion: To examine this association in the South African Currie Cup rugby union competition, time-loss (≥ 1 day training/match play missed) injury data and final position in the competition was examined over five-seasons. Teams who ranked in 1st position had significantly lower average injury rates than teams who ranked in last position [48 injuries per 1 000 player hours (95% C.I 20 to 76) vs 130 injuries per 1 000 player hours (95% C.I 79 to 180)]. More specifically, the team with the lowest injury rate in each season ranked in 1st or 2nd position. This team performance aspect of injury prevention should be highlighted more. In particular, this should be used to assist with communicating the importance of injury prevention programmes to stakeholders directly involved with budgetary allocations in the team.